2020
DOI: 10.1111/jbi.13992
|View full text |Cite
|
Sign up to set email alerts
|

Blow to the Northeast? Intraspecific differentiation of Populus davidiana suggests a north‐eastward skew of a phylogeographic break in East Asia

Abstract: AimThere is increasing interest in the role that biological traits, and historical and biogeographic processes, play in the formation of phylogeographic patterns. An arid belt that once existed in northern China might have affected many plants, but this has yet to be tested in an arid‐tolerant, wind‐dispersed species. Here, we tested how intrinsic and extrinsic factors have affected the phylogeography of Populus davidiana.LocationEast Asia.MethodsGenetic variation was surveyed across 40 populations (555 indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…Similar phylogeographic breaks in northern China have been also demonstrated for several other species, including Acer mono , Populus davidiana and Lindera obtusifolia (Guo et al ., 2014; Liu et al ., 2014; Zong et al ., 2015; Bai et al ., 2016; Ye et al ., 2017; Song et al ., 2020). The breaks are generally attributed to the climatic barrier of the arid belt since the late Miocene (Milne & Abbott, 2002), and the Pleistocene glaciation appeared to intensify the isolation between two sides of the belt where populations persisted in multiple refugia (Chen et al ., 2008; Tian et al ., 2009; Bai et al ., 2010; Guo et al ., 2014; Ye et al ., 2017; Song et al ., 2020). During the interglacial periods, hybrid zones were formed through range expansion as well as pollen/seed mediated gene flow.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar phylogeographic breaks in northern China have been also demonstrated for several other species, including Acer mono , Populus davidiana and Lindera obtusifolia (Guo et al ., 2014; Liu et al ., 2014; Zong et al ., 2015; Bai et al ., 2016; Ye et al ., 2017; Song et al ., 2020). The breaks are generally attributed to the climatic barrier of the arid belt since the late Miocene (Milne & Abbott, 2002), and the Pleistocene glaciation appeared to intensify the isolation between two sides of the belt where populations persisted in multiple refugia (Chen et al ., 2008; Tian et al ., 2009; Bai et al ., 2010; Guo et al ., 2014; Ye et al ., 2017; Song et al ., 2020). During the interglacial periods, hybrid zones were formed through range expansion as well as pollen/seed mediated gene flow.…”
Section: Discussionmentioning
confidence: 99%
“…During the interglacial periods, hybrid zones were formed through range expansion as well as pollen/seed mediated gene flow. These species varied in locations and ranges of hybrid zones, possibly because the species had different degrees of gene flow and different levels of tolerance to aridity (Song et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, Meng et al (2015) have suggested the CLP to be an important refugium for the dry-adapted flora of northwestern China. Furthermore, disjoint distribution of same haplotype between CLP and northeastern China may result from long distance dispersal from the CLP ( Tian et al, 2009 ; Song et al, 2020 ). Finally, haplotypes of S. tuberculata in the Sichuan Basin (H13–14) are derived from the ancestral haplotype (H1), indicating the CLP may be the source of genotypes in southwestern China.…”
Section: Discussionmentioning
confidence: 99%